The Effect of Uncertainty on Saving Decisions - Sandmo, A. (Review of Economic Studies, 1970)
Journal Article The Effect of Uncertainty on Saving Decisions Get access A. Sandmo A. Sandmo The Norwegian School of Economics and Business Administration Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 37, Issue 3, July 1970, Pages 353–360, https://doi.org/10.2307/2296725 Published: 01 July 1970 Article history Received: 01 October 1968 Revision received: 01 May 1969 Published: 01 July 1970